Characterization of sarcopenia with ultrasound-based measurements in patients with advanced chronic liver disease. (March 2023) - Gallo, P.; Flagiello, V.; De Vincentis, A.; Terracciani, F.; Picardi, A.; Incalzi, R. Antonelli; -Gentilucci, U. Vespasiani
Abstract : Introduction: Sarcopenia is a very common complication of cirrhosis. In the clinical setting, it is usually diagnosed using operational definitions based on low muscle mass. Muscle ultrasound-based measurement has recently achieved attention because of its easier feasibility; however, only a few studies evaluating this approach have been reported. Aim: We aimed to validate ultrasound-derived measurements for the assessment of sarcopenia in a cohort of patients with chronic liver disease (CLD) evaluated by computed tomography (CT) or magnetic resonance imaging (MR) during follow-up for hepatocellular carcinoma (HCC). Materials and methods: Consecutive adult outpatients attending our Hepato-Oncology Unit were included in the study. CT\MR scans were imported and analysed, and the L3-skeletal mass index was calculated. Ultrasound was performed to obtain muscle thickness and derived indices according to different previously described techniques. Receiver operating characteristic (ROC) curve analysis was performed to assess the diagnostic accuracy of each technique with respect to sarcopenia as determined by CT and/or MR analyses. Results: 51 patients were included. The average age was 74 years (±7.07), with a prevalence of male gender (70.6%). Mean BMI was 27.4 kg/m2. The most common etiology of cirrhosis was metabolic (41.2%), and more than half of the patients (68%) had a preserved liver function. Logistic regression analysis identified the average feather index [OR 13.64 (1.25-196.17), p 0.04] and the ileopsoas(IP)-index [OR 1.01 (1-1.02), p 0.01] as significantly associated with a low muscle mass expressed with CT/MR. The IP-index was the only one showing an adequate discriminative ability, with an AUROC of 0.79 (0.65-094) (Figure 1). Conclusions: Our preliminary results show a statistically significant association between some ultrasound-based techniques and reduced muscle mass. If these results will be confirmed in larger and external series, ultrasound would represent a feasible and cheap tool for assessing sarcopenia at least in patients with CLD.